New species and new record of Cerambycidae (Coleoptera) from Mexico, with updates to type depository for two species of Disteniinae - Heffern, Daniel; Santos-Silva, Antonio (Zootaxa, 2016)
Three new species are described from Mexico belonging to two different subfamilies: Derobrachus moroni (Prioninae); Elytrimitatrix (Grossifemora) nogueirai, and E. (G.) cunninghami (Disteniinae). The new species are illustrated and included in existing keys. A new country record is given for Neomallodon arizonicus (Casey, 1912) (Prioninae). The type depository is corrected for two species of Disteniinae.